Spatiotemporal variation characteristics of extreme temperature events in Hainan Province over the past four decades - Yun, Qiuhao; Zhang, Qiang (Frontiers in Environmental Science, 2025)
IntroductionGlobal warming has led to an increase in the frequency and intensity of extreme weather events. In Hainan Province, a key tropical agricultural region in China, extreme temperatures significantly affect crop yields, quality, and the sustainability of the agricultural economy. Understanding the temporal and spatial patterns of extreme temperature events in Hainan Province is crucial for formulating effective strategies for mitigating meteorological disasters and safeguarding agricultural productivity.MethodsThis study uses observational data from 21 meteorological stations in Hainan Province from 1980 to 2022. Eight extreme temperature indices were calculated using the RClimDex model. Temporal and spatial characteristics of extreme temperature events were analyzed through linear fitting, Mann-Kendall mutation tests, Morlet wavelet analysis, and principal component analysis.ResultsThe results reveal that extreme temperature events in Hainan Province show an overall increasing trend over time. Spatially, most stations exhibit a similar increasing trend in extreme temperature events. Two indices, Maximum Daily Temperature of the Year (TXx) and Number of Days with Lowest Temperature >20°C (TR20), display upward mutations, particularly between 2000 and 2011. Additionally, cyclical patterns in extreme temperature indices include short (4 years), medium (8–14 years), and long (16–20 years) oscillatory cycles.DiscussionThe study highlights that the primary drivers of temperature variations in Hainan Province are warm temperature indicators, with significant changes in daily maximum temperatures playing a key role. These findings emphasize the need for further investigation into the long-term effects of temperature variations on agricultural production and suggest potential pathways for disaster mitigation and adaptation strategies in the region.